Dynamics of Political Resistance in Tibet: Religious Repression and Controversies of Demographic Change. (March 2014) - Han, Enze; Paik, Christopher
Abstract In a novel approach to studying political mobilization among ethnic Tibetans in China, this article addresses two key questions. First, considering the Chinese state's repressive policies towards Tibetan Buddhism, what role does religion play in fomenting Tibetan political resistance? Second, what implications can be drawn from the changing ethnic demography in Tibet about the conflict behaviour of Tibetans? Using various GIS-referenced data, this article specifically examines the 2008 Tibetan protest movements in China. The main results of our analysis indicate that the spread and frequency of protests in ethnic Tibetan areas are significantly associated with the number of officially registered Tibetan Buddhist sites, as well as the historical dominance of particular types of Tibetan religious sects. Furthermore, our analysis shows that the effect of Han Chinese settlement on Tibetan political activism is more controversial than previously thought.